Android-Based Digital Mathematics Learning Media For Elementary School Students: Preliminary Study - Fitriani, Elya; Roemintoyo, Roemintoyo; Sarwanto, Sarwanto (Universitas Sebelas Maret, 2023)
Mathematics is a subject that is less attractive to students because it is con-sidered difficult to solve the problems, plus when learning they are often lazy which can cause many problems such as lack of understanding of con-cepts, not developing creative thinking patterns, and decreased academic achievement. Therefore, this study intends to identify the needs of Android-based digital learning media that are able to facilitate students learning math-ematics in a more fun and participatory way. The research method is quanti-tative research, with the data collection instrument, namely a questionnaire. The sample involved in this research consisted of 17 fifth grade elementary school students (5). Responses from the questionnaire were then analyzed descriptively with percentages. The results of this research indicate that stu-dents are used to using Android smartphones, they also often use them, only not for learning but for watching YouTube and playing games. Most of them also want a learning application with the material content being mathematics, so they can learn the material when at home, and in the end students have more time to study than watching Youtube when playing their smartphones, so it is necessary to develop an Android-based learning media for mathematics.